IOT STATUS COMMUNICATION FOR HOME AUTOMATION - Steane, Tyler Nicholas Edward; Radcliffe, PJ (International Journal of Computing, 2019)
The vast majority of home automation systems depend on a permanent central controller and this is the source of many serious problems. The controller may be eliminated by using one or more Intermittent Control Devices such as a smartphone, but the responsibilities of the controller must be redistributed. This paper considers the problem of keeping multiple intermittent controllers up-to-date with status information for devices around the home. Four protocols are proposed, taking key lessons from existing network protocols, and then implemented, tested and compared with the expected performance of UPnP. All four protocols outperform UPnP and further analysis shows that these protocols can be implemented in a robust and user-friendly manner. A comparison of the packet efficiency of these protocols demonstrates that the combination of device registration and packet broadcasting makes for the most efficient protocol and should form the basis of devices status communications in home automation systems without a permanent central controller.